Penerapan Metode Deep Flow Technique Dan Floating Raft Terhadap Pertumbuhan Dan Hasil Dua Varietas Pakcoy (Barissca rapa L.). - feri adi kurniawan; Agus Sugianto; Siti Muslikah (AGRONISMA, 2022)
Pakcoy plant is a leaf vegetable that is widely cultivated with urban Farming technology because it has high economic value. Urban Farming is a technology by utilizing narrow land for crop cultivation. One of the technologies of urban farming is the hydroponic method. Hydroponics is a planting method needed by plants by not using soil as a binder to various nutrients needed by plants. This study aims to determine the differences in hydroponic methods of DFT and floating rafts in green and red pakcoy plant varieties as well as against growth and yield. The design used is a factorial RPT consisting of two factors. The first factor of the hydroponic method consists of two levels (DFT and Floating raft). The second factor is that the pakcoy variety consists of two levels (green and red pakcoy). The results showed that the combination of the treatment of the floating raft method and green pakcoy had the highest value at the parameters of plant height of 21.70 cm, number of leaves 12.08 leaf blade, leaf area of 1233.24 cm2, root length of 279.11 mm, root volume of 11.39 ml, total fresh weight of 191.48 grams/plant, fresh weight of consumption of 180.12 grams/plant, total dry weight of 39.23 grams/plant, and dry weight consumption of 33.74 grams/plant,Â  while the harvest index parameter of 95.01% is found in the treatment of the DFT and green pakcoy methods.Keywords: DFT, Hydroponics, Â Green Pakcoy, Red Pakcoy, Floating Raft.